Data collection about failures in fixed partial dentures: 1-year monitoring - Adriana Cristina ZAVANELLI; José Vitor Quinelli MAZARO; Pâmella Izza NÓBREGA; Rosse Mary FALCÓN-ANTENUCC; Ricardo Alexandre ZAVANELLI (Faculdade São Leopoldo Mandic, 2018)
Objective: The aim of this study was to evaluate the satisfaction of patients rehabilitated with fixed partial denture and the incidence of failures/clinical complications of prostheses after one year. Methods: The patients answered a questionnaire about the satisfaction degree with dental treatment performed and care maintenance for prosthesis conservation. Clinical and radiographic evaluations of the prosthesis were performed. Data were tabulated for descriptive analysis of the factors assessed, with calculation of absolute frequencies and percentages, and chi-square and Fisher's exact test. Results: A total of 9.67% failures were found. The most common was the prosthesis loosening (57.14%), followed by ceramic fracture (28.57%), and abutment tooth fracture (14.29%). Biological failures were observed in 30.65%. The most common failure was gingival recession (52.00%), periodontal pocket (24.00%), support periodontal involvement (16.00%), and recurrent caries (4.00%). Radiographic examination showed that 70.97% of the total number evaluated had some kind of failure. There was statistically significant association between satisfaction degree and technical failure (p=0.04). Conclusion: Patients were satisfied after observation period of 1 year. The main failures detected were: crown cementation failure and ceramic fracture; gingival recession, periodontal pocket; manufacture and cementation of short intraradicular post with increased diameter and crown cervical misfit.